METABOLIC SYNDROME AND RISK OF STROKE IN THE POPULATION OF NOVOSIBIRSK - S. V. Shishkin; S. V. Mustafina; L. V. Shcherbakovа; G. I. Simonova (Кардиоваскулярная терапия и профилактика)
Aim. To explore the association between Metabolic Syndrome (MS) and risk of stroke in Novosibirsk citizens aged 45–69 years.Material and methods. As a part of an international prospective cohort HAPIEE study the population sample of 9363 residents of Novosibirsk aged 45–69 years were surveyed by screening method.Results. A high prevalence of metabolic disorders in the population was revealed; the levels and distribution of cardiometabolic factors in first-ever stroke examined. It was found by the “case-control” study, that the combination of hypertension and abdominal obesity (AO) increases the odds ratio (OR) for stroke in the population studied.Conclusion. It was shown to 2-fold increase in the risk of stroke in people with MS by 9-year prospective observation. Prognostic models of combining components of MS affecting the OR of stroke were identified in an urban population of Siberia.